Utilizing Serious Games as an Interactive Platform for Programming Learning in Informatics Students - Wicaksono, Manuel Yosia Krista Ananda; Prasetya, Noven Indra (Universitas Muhammadiyah Ponorogo, 2025)
Programming is a critical skill for informatics students, enabling them to design systems, develop software, and analyze user requirements. However, many students face significant challenges in understanding programming concepts and syntax, particularly during the initial stages of learning. These difficulties often stem from limited proficiency in reading, debugging, and writing code, coupled with low motivation and engagement in the learning process. To address these challenges, it is essential to adopt engaging and enjoyable instructional approaches. Serious games have proven to be an effective instructional method, enhancing students' motivation and engagement through game-based elements. This study introduces DolananCoding, a serious game developed as an interactive platform for teaching structured programming courses. DolananCoding incorporates two key features: live coding and a leaderboard, both designed to boost students' motivation and engagement in programming learning. The platform was rigorously evaluated through two testing methods: system testing and user testing. System testing validated the fulfillment of functional requirements, including modules, materials, and experience points, all of which met the expected standards. User testing assessed the platform's user satisfaction through a questionnaire administered to 76 students, yielding an average satisfaction score of 4.3 out of 5.0. These results indicate a positive reception among students, demonstrating the platform's readiness for integration into programming learning.